Understanding contemporary strategy - Lonsdale, David J., author.
1 online resource
Keywords: "This textbook provides a comprehensive introduction to modern strategy, covering the context, theory and practice of military strategy in all its different forms. Covering all the main issues in the field, the book explores the major themes through a combination of classical and modern strategic theory, history and current practice. It is split into three main sections: The first provides the context for contemporary strategy, and includes discussions of the human, technological, intelligence, ethical and grand-strategic dimensions. The second part explores the theory and practice of strategy in different geographical domains, including land, sea, air, space, and cyberspace. The final part engages with three of the most challenging forms of strategy in the contemporary era: nuclear weapons, terrorism, and insurgency. This updated second edition brings the book up to date by including discussions of the rise and fall of ISIS; the emergence of robotics and artificial intelligence; major events in space and cyberspace; and the growing profile of nuclear weapons. Each chapter presents the reader with a succinct summary of the topic, provides a challenging analysis of current issues, and finishes with key points, questions for discussion, and further reading. This book will be essential reading for upper-level students of strategic studies, war studies, military history and international security."--